2003
DOI: 10.1016/s0924-9338(03)00065-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function in obsessive-compulsive disorder: effects of comorbid conditions on task performance

Abstract: Findings are consistent with the contention that dysfunction of an orbitofrontal-limbic network underlies OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 46 publications
4
68
1
2
Order By: Relevance
“…In addition, Boldrini et al [2005] reported that visuoconstructive deficits seemed specific in OCD and supported the ventral frontostriatal circuit involvement in OCD. According to Aycicegi et al [2003], patients with OCD demonstrated performance deficits on measures of some neuropsychological tests, including visuoconstructional ability, that were consistent with the contention that dysfunction of the orbitofrontal-limbic network underlies OCD. However, Shin et al [2004] reported that using a qualitative scoring system for the ROCF, patients with OCD had impairments only in planning and organization, not in visuoperceptual and visuoconstructional ability during copying.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, Boldrini et al [2005] reported that visuoconstructive deficits seemed specific in OCD and supported the ventral frontostriatal circuit involvement in OCD. According to Aycicegi et al [2003], patients with OCD demonstrated performance deficits on measures of some neuropsychological tests, including visuoconstructional ability, that were consistent with the contention that dysfunction of the orbitofrontal-limbic network underlies OCD. However, Shin et al [2004] reported that using a qualitative scoring system for the ROCF, patients with OCD had impairments only in planning and organization, not in visuoperceptual and visuoconstructional ability during copying.…”
Section: Discussionmentioning
confidence: 57%
“…In order to achieve a favorable outcome in the IGT, initially-acquired preference toward the disadvantageous decks should be suppressed, which may rely on reversal learning (Fellows and Farah, 2005;Maia and McClelland, 2004). In OCD, previous studies have suggested impaired reversal learning in line with orbitofrontal dysfunction (Abbruzzese et al, 1997;Aycicegi et al, 2003;Remijnse et al, 2006), but contradictory findings also exist (Chamberlain et al, 2007;Kuelz et al, 2004). Given the critical role of the orbitofrontal cortex in the pathophysiology of OCD, we hypothesized that impaired reversal learning would affect IGT performance in patients with OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that patients with OCD exhibit extensive cognitive functional dysfunction including the domains of attention, memory, abs tract thinking, and spatial memory 6,7 . Research has shown that OCD patients with depression have obviously decreased executive function 8 . In this study, cognitive functional testing revealed that the performance of patients with OCD for the total number of correct responses, total error number, preservative error number, and number of categories was much worse than that of the control group, which demonstrates that attention and executive function were impaired in patients with OCD.…”
Section: Discussionmentioning
confidence: 99%